Women’s Land Rights: A Status Review - Durai, Kalpana (Journal of Advanced Research in English & Education; Vol 9 No 2 (2024): Journal of Advanced Research in English & Education, 2024)
This article explores the intricate relationship between land reforms, caste, and gender in India, particularly in Tamil Nadu against the backdrop of broader socio-economic development goals. Land reform policies in India initiated post-independence, aimed to dismantle the feudal land ownership structures and redistribute land to marginalised communities. However, the implementation of these reforms has been inconsistent, and their impact on Dalits and women has been particularly complex and varied. By examining historical reports, government policies, and academic research, this article analyses the effectiveness of land reforms in promoting socio-economic equity. It delves into the caste-based disparities in land ownership and highlights the limited success of reforms in truly empowering Dalits. Furthermore, the article underscores the gendered dimension of land ownership, revealing how patriarchal norms continue to hinder women’s access to land despite legal provisions for gender equity. Case studies from Tamil Nadu are utilised to illustrate the ground realities and challenges faced by marginalised groups in securing land rights. The article also critiques the existing policy framework and suggests the need for more inclusive and effective strategies that address both caste and gender biases in land distribution and ownership. In conclusion, the article calls for a re-evaluation of land reform policies with a focus on intersectionality, ensuring that future reforms are not only just in theory but also equitable in practice, thereby contributing to the broader goals of social justice and sustainable development. Keywords: Women’s Land Rights, Caste and Gender, Land Reforms. Feudal Land Ownership, Marginalised Communities. Dalits, Patriarchal Norms, Socio-Economic Equity, Intersectionality, Social Justice, Sustainable Development, Land Governance, Land Inequality, Land Ownership, Economic Exploitation, Rural Women, Land Distribution, Social Disparities